PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MELALUI MODEL THINK PAIR SHARE BERBANTUAN MEDIA MONOPOLI BUDAYA PADA SISWA KELAS V SDN MUKTIHARJO KIDUL 03 - Dina Mustafida; Farida Nursyahidah; Suyoto; Maflakhah (STKIP Subang, 2023)
The type of research used in this study was Classroom Action Research which was carried out in 2 cycles, each cycle consisting of 2 meetings. Each cycle consists of 4 stages, namely planning, implementing, observing, and reflecting. The subjects in this study were fifth grade students at SDN Muktiharjo Kidul 03, totaling 16 students consisting of 6 male students and 10 female students. The focus of this research is the improvement of teachers' teaching skills and students' critical thinking. The test was tested using expect judgment validation, while the data analysis used was quantitative and qualitative analysis. The results showed an increase in students' critical thinking in cycle I reached 78.9 with classical completeness reaching 63% in the sufficient category, while in cycle II the results of students' critical thinking abilities classically reached 85.4 with classical completeness reaching 88% in the good category. This proves that increasing critical thinking can be improved through the Think Pair Share model assisted by Monopoly media learning in class V SDN Muktiharjo Kidul 03. Based on the results of class action research conducted in class V SDN Muktiharjo Kidul 03 it can be concluded that students' critical thinking can be increased through the model assisted by Think Pair Share media assisted by Mobudus media in class V SDN Muktiharjo Kidul 03. The researcher suggests that in applying the Think Pair Share model assisted by Mobudus media teachers must be more skilled and innovative in increasing student participation in learning activities.